Musculoskeletal adverse events in dogs receiving bedinvetmab (Librela) - Farrell, Mike; Waibel, Felix W. A.; Carrera, Ines; Spattini, Giliola; Clark, Louise; Adams, Robert J.; Von Pfeil, Dirsko J. F.; De Sousa, Ricardo J. R.; Villagrà, Diego Bobis; Amengual-Vila, Maria; Paviotti, Annalisa; Quinn, Rob; et al. (Frontiers in Veterinary Science, 2025)
ObjectivesTo conduct a specialist-led disproportionality analysis of musculoskeletal adverse event reports (MSAERs) in dogs treated with bedinvetmab (Librela™) compared to six comparator drugs with the same indication. Furthermore, to report the findings from a subset of dogs whose adverse event (AE) data underwent independent adjudication by an expert panel.Study designCase–control study and case series analysis.Sample populationThe European Medicines Agency’s EudraVigilance database (2004–2024) and 19 client-owned dogs.MethodsAn EBVS® Veterinary Specialist in Surgery individually reviewed all MSAERs to Librela™, Rimadyl®, Metacam®, Previcox®, Onsior®, Galliprant®, and Daxocox® (2004–2024). The primary null hypothesis was that Librela’s MSAER rate would not exceed that of comparator drugs by more than 50%. The secondary hypothesis was that MSAER would surge and taper following the launch of new drugs.ResultsThe disproportionality analysis did not support the hypotheses. Ligament/tendon injury, polyarthritis, fracture, musculoskeletal neoplasia, and septic arthritis were reported ~9-times more frequently in Librela-treated dogs than the combined total of dogs treated with the comparator drugs. A review of 19 suspected musculoskeletal adverse events (MSAEs) by an 18-member expert panel unanimously concluded a strong suspicion of a causal association between bedinvetmab and accelerated joint destruction.ConclusionThis study supports recent FDA analyses by demonstrating an increased reporting rate of musculoskeletal adverse events in dogs treated with Librela. Further investigation and close clinical monitoring of treated dogs are warranted.ImpactOur findings should serve as a catalyst for large-scale investigations into bedinvetmab’s risks and pharmacovigilance.